Nurses' Knowledge Regarding The Management Of Invasive Mechanical Ventilation: Integrative Review - De Novaes, Matheus Da Silva; Mansano, Victoria Adryelle Nascimento; Zulin, Aline; Frez, Flávia Cristina Vieira; Vieira, Viviane Cazetta de Lima; Radovanovic, Cremilde Aparecida Trindade; Gil, Nelly Lopes de Moraes; Back, Ivi Ribeiro; Uema, Roberta Tognollo Borotta; Rodrigues, Thamires Fernandes Cardoso da Silva (Seven Editora, 2023)
to identify in the literature the nurses' knowledge regarding the management of invasive mechanical ventilation. Metodologia: Trata-se de uma revisão integrativa que contemplou estudos publicados entre janeiro de 2017 a maio de 2022, disponíveis na integra eletronicamente, com enfoque em adultos, não restringindo o idioma, a localidade de origem das produções e o método utilizado. Thematic analysis was adopted and the data were operationalized by the Iramuteq® software. Results: nine studies were found that approached the theme. From the analysis three classes emerged, being: 1st Class: (Un)Knowledge about the care of patients under mechanical ventilation in Intensive Care Unit; 2nd Class: Educational strategies for the qualification of professionals who act in the care of patients under mechanical ventilation; and 3rd Class: Professional autonomy of nurses for the decision making in the care of patients under MV. Final considerations: a gap was identified in the formation and qualification of nurses to develop nursing care with quality, safety and autonomy. The nurse plays a relevant role in the management of patients on mechanical ventilation, acting in three pillars considered essential: care, management and education/research. DOI: https://doi.org/10.56238/colleinternhealthscienv1-094